The forms and bioavailability of phosphorus in integrated vertical flow constructed wetland with earthworms and different substrates. (September 2015) - Xu, Defu; Wang, Lin; Li, Huili; Li, Yingxue; Howard, Alan; Guan, Yidong; Li, Jiuhai; Xu, Hui
Highlights: Addition of earthworms increased the Ex-P, Fe-P, Ca-P, Oc-P, De-P and Org-P content. Addition of earthworms into IVFCW increased the bioavailable P content. The bioavailable P forms in IVFCW were influenced by type of substrates. Abstract: A sequential extraction method was utilized to analyze seven forms of P in an integrated vertical-flow constructed wetland (IVFCW) containing earthworms and different substrates. The aluminum-bound P (Al-P) content was found to be lower, and the occluded P (Oc-P) content was higher in the IVFCW. The addition of earthworms into the influent chamber of IVFCW increased the exchange P (Ex-P), iron-bound P (Fe-P), calcium bound P (Ca-P), Oc-P, detritus-bound (De-P) and organic P (Org-P) content in the influent chamber, and also enhanced P content uptake by wetland plants. A significantly positive correlation between P content of above-ground wetland plants and the Ex-P, Fe-P, Oc-P and Org-P content in the rhizosphere was found ( P < 0.05), which indicated that the Ex-P, Fe-P, Oc-P and Org-P could be bio-available P. The Ex-P, Fe-P, De-P, Oc-P and Ca-P content of the influent chamber was higher where the substrate contained a mixture of Qing sand and river sand rather than only river sand. Also the IVFCW with earthworms and both Qing sand and river sand had a higher removal efficiency of P, which was related to higher P content uptake by wetland plants and P retained in IVFCW. These findings suggest that addition of earthworms in IVFCW increases the bioavailable P content, resulting in enhanced P content uptake by wetland plants.